The Influence of BTS as Tokopedia Brand Ambassador on Customer Loyalty - Nabilla, Zulfa; Prasetyawati, Happy (CV. Proaksara Global Transeduka, 2024)
In this modern era, the use of the internet seems to be human daily food. There is no day without opening the internet, starting from news, information, entertainment and even shopping can be accessed via the internet. Tokopedia is an e-commerce that is quite influential in Indonesia today, this cannot be separated from a marketing communication strategy which is a tool to influence others, provide information and spread the promotion in marketing activities so that success occurs within the company. Tokopedia made Bangtan Sonyeondan or BTS, commonly known as its brand ambassador, as a marketing communication strategy in improving the brand image and loyalty of Tokopedia customers. The current study aims to determine the effect of BTS as a Brand Ambassador at Tokopedia on customer loyalty. The theory used in this research is Uses And Gratification theory. The results of the study show that BTS as Tokopedia's Brand Ambassador has a positive and significant influence on Customer Loyalty.